Generalforsamling i Steno Museets Venner den 28. marts 2000 kl. 19.30 på Steno Museet - Grøn, Bjarning (Stenomusen, 2020)
Generalforsamling i Steno Museets Venner den 28. marts 2000 kl. 19.30 på Steno Museet